BIOFILIA DAN NEKROFILIA: ANAL ISIS SOSIOLOGI SASTRA NOVEL LA BETE HUMAINE KARYA EMILEZOLA - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Based on the analysis of genetic structuralism suggested by Lucien Goldmann, showed that Emile Zola as an adherent of naturalism, through the mediation of his work LaReteHumaine, has managed to bring a distinctive world view. In his career as an author who engage fully in social and political life of his time, Zola has been firmly demonstrated a world view that is different with the rulers at that time. His involvement in the political field, as well as to the weak, and become victims of an unjust system of capitalism, and his commitment to the truth which he believed, had produced changes in the field of social and political. This is evident with the recognition of social rights of workers in those days, and the .release of Alfred Dreyfus from prison. Yet all that must be redeemed by his life. Zola died of assassinated by political opponents.